Analisis Kinerja Keuangan Anggaran Pendapatan Belanja Daerah Kabupaten Teluk Wondama Periode 2017 - 2021 - Tety Lensiana Mandua; Camelia L. Numberi; Simson Werimon (Lensa Ekonomi, 2022)
This study uses financial ratio analysis to evaluate the effectiveness of the management of the Wondama Bay regional revenue and expenditure budget for 2017–2021. Descriptive qualitative research is such. The report on the realization of the Teluk Wondama Regency APBD for the 2017–2021 period as a secondary data source, and documentation as a data collection method. Based on the findings of the financial ratio analysis, the overall performance of the Wondama Bay Regency APBD Manager for the 2017-2021 period is as follows: (1). Financial performance analysis Unexpected differences or smaller differences occur in revenue growth. (2). The level of decentralization is still quite low. (3) Regional financial independence is still quite low. (4). Still not effective is effectiveness. (5). Efficiency is now experiencing efficiency.